2004
DOI: 10.1530/eje.0.1500691
|View full text |Cite
|
Sign up to set email alerts
|

Increase of serum leptin after short-term pulsatile GnRH administration in children with delayed puberty

Abstract: Objective: Leptin is known to play an important role in pubertal development in humans, probably acting as one permissive factor for the onset of puberty. Leptin serum concentrations change during pubertal development and an initial increase before the onset of puberty has been reported. The underlying mechanism for this increase in leptin levels is unknown. We hypothesized that the pulsatile release of GnRH stimulates leptin metabolism. In this study, the effect of short-term pulsatile GnRH administration on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…GarciaMayor found that female puberty leptin concentrations steadily increase whereas in male puberty leptin concentrations only increase until approximately the age of 10 years, and then decrease with increasing testosterone levels (Garcia-Mayor et al, 1997). Interestingly, it has been shown that leptin levels peak before the onset of puberty in both sexes, suggesting a specific role for leptin at this point of puberty (Horlick et al, 2000;Mantzoros et al, 1997;Grasemann et al, 2004). Endocrinologist Jeffrey Flier of the Beth Israel Deaconess Medical Center in Boston proposed that leptin may even be the trigger for the onset of puberty (Vogel, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…GarciaMayor found that female puberty leptin concentrations steadily increase whereas in male puberty leptin concentrations only increase until approximately the age of 10 years, and then decrease with increasing testosterone levels (Garcia-Mayor et al, 1997). Interestingly, it has been shown that leptin levels peak before the onset of puberty in both sexes, suggesting a specific role for leptin at this point of puberty (Horlick et al, 2000;Mantzoros et al, 1997;Grasemann et al, 2004). Endocrinologist Jeffrey Flier of the Beth Israel Deaconess Medical Center in Boston proposed that leptin may even be the trigger for the onset of puberty (Vogel, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Another significant finding was the observed increase in GnRH mRNA expression in male offspring as a result of parental adolescent binge EtOH exposure. GnRH has long been known for stimulation of gonadotropin release from the pituitary gland in both males and females and therefore, is absolutely required for pubertal onset and fertility [43], [44], [45], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80]. Recently, a role for GnRH in metabolic functions has been demonstrated by Harris and colleagues, who showed that GnRH increased the expression of the glucose transporter, GLU-1, in pituitary gonadotrophs and stimulated glucose uptake in these cells [81].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery that leptin levels are correlated with the onset of puberty revealed a key conduit by which nutrition influences sexual maturation [18,19,47,48]. Leptin is secreted by adipocytes, and serum leptin levels, proportional to body fat, are thought to signal nutritional status to the hypothalamus and thus help govern appetite and energy expenditure.…”
Section: Introductionmentioning
confidence: 99%